2020
DOI: 10.1101/2020.12.22.424019
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid 40 kb genome construction from 52 parts

Abstract: Large DNA constructs (>10 kb), including small genomes and artificial chromosomes, are invaluable tools for genetic engineering and vaccine development. However, the manufacture of these constructs is laborious. To address this problem, we applied new design insights and modified protocols to Golden Gate assembly. While this methodology is routinely used to assemble 5-10 DNA parts in one-step, we found that optimized assembly permitted >50 DNA fragments to be faithfully assembled in a single reaction. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…By Golden Gate assembly, 40 kb genome of T7 phage was constructed from 52 DNA fragments. 38 Combining iPac with Golden Gate assembly may improve the efficiency of multifragment construction. Here, I demonstrated the construction of the phage genomes and the large plasmids using portions of phage genomes as DNA fragments.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…By Golden Gate assembly, 40 kb genome of T7 phage was constructed from 52 DNA fragments. 38 Combining iPac with Golden Gate assembly may improve the efficiency of multifragment construction. Here, I demonstrated the construction of the phage genomes and the large plasmids using portions of phage genomes as DNA fragments.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It is probable that this factor outweighs the costs of reduced reaction volume. Pryor et al recently demonstrated the use of Golden Gate assembly to efficiently assemble a 40 kbp bacteriophage genome from 52 parts . These data suggest that the EMMA pipeline is likely to be able to handle far larger constructs.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR amplicons were gel purified and mixed with the entry vector. They were assembled together using Golden Gate assembly with Bsm BI 44 . The final plasmids were confirmed by Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…They were assembled together using Golden Gate assembly with BsmBI 44 . The final plasmids were confirmed by Sanger sequencing.…”
Section: Creepy Plasmids and Grna Assemblymentioning
confidence: 99%